Transformasi Digital: Pendampingan Pemasaran dan Rebranding untuk Kesuksesan UMKM - Fitri Umardiyah; Anita Rohmatul Ummah; Noviana Nur Sholihah; Iin Baroroh Ma'arif; Novia Ayu Sekar Pertiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2024)
Businesses use the internet as a source of information and as a marketing and sales tool. Digital sales and marketing can also reach more potential consumers. The rapid phenomenon of digital information has become a place to shift a business from conventional sales and marketing to digital. However, not all business activists have been able to keep up with changes in the flow of digitalization. This also happens to MSME activists in Kudubanjar Village. The main objective of this PKM activity is to help MSME activists who do not understand the importance of digital sales and marketing and are able to brand their products. PKM activities were carried out in two stages, namely a workshop which was held on August 8, 2024 and mentoring which was carried out on August 12-15, 2024, August 19-22, 2024 and August 27, 2024. The results obtained are that MSME activists understand what branding and digital marketing are, can make logo designs, and can promote products through WhatsApp Bussines.